Islam in Xinjiang: Geopolitical and Ethnocultural Drivers of Social and Cultural Formation - Makhmet, Muratkhan; Yerzhan, Kalmakhan; Mukhitdinov, Rashid; Kaliyev, Kaskyrbek; Kamysbek , Ularbek (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This article analyzes the main geopolitical and ethnocultural factors that influenced the spread and social embedding of Islam in Xinjiang (also referred to in some historical usages as East Turkestan). To address the recurrent mismatch between region-wide claims and community-specific evidence, the study adopts an explicitly comparative lens: it draws on the substantial English-language scholarship on Uyghur religious history and authority formation, while also integrating Kazakh- and Russian-language historiography and regional publications on Kazakh communities in Xinjiang as an analytically important minority case. Using a historical-comparative design complemented by geopolitical analysis and content analysis, the article applies a four-phase periodization and examines each phase through common explanatory lenses: (1) geopolitical setting and external linkages, (2) political power and elite incentives, (3) religious authority networks and institutions (including Sufi lineages), and (4) ethnocultural boundary-making and cultural production. The findings support a multi-driver account of Islamization in which connectivity, elite sponsorship, and authority infrastructures interact, with driver salience shifting across historical phases. By reducing language segmentation in the field and distinguishing majority (Uyghur) and minority (Kazakh) configurations, the study offers a mechanism-oriented synthesis and identifies priorities for future comparative research on Islam, ethnicity, and governance in Xinjiang.